2019
DOI: 10.1002/14651858.cd013449
|View full text |Cite
|
Sign up to set email alerts
|

Myofunctional therapy (oropharyngeal exercises) for obstructive sleep apnoea

Abstract: Myofunctional therapy (oropharyngeal exercises) for obstructive sleep apnoea (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…MT is a promising treatment for SDB and is based on daily exercises to strengthen the oropharyngeal muscles and facilitate the opening of the airway [6][7][8][9][10][11][12][13]. However, the main drawbacks of MT are the low adherence, which has been reported to be as low as 10% [18][19][20][21], and the absence of objective feedback [9,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MT is a promising treatment for SDB and is based on daily exercises to strengthen the oropharyngeal muscles and facilitate the opening of the airway [6][7][8][9][10][11][12][13]. However, the main drawbacks of MT are the low adherence, which has been reported to be as low as 10% [18][19][20][21], and the absence of objective feedback [9,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, because OSAHS originates from the suboptimal function of the dilator muscles of the airway, MT is designed, theoretically, to treat the mechanism underlying this disease. Several papers have reported its effectiveness, including randomized controlled trials, meta-analyses, and reviews [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent meta-analysis evaluating the benefits of myofunctional therapy for the treatment of OSA, the authors concluded that myofunctional therapy may reduce daytime sleepiness and may increase sleep quality in the short term, and the certainty of the evidence ranges from moderate to very low, due to a lack of blinding, incomplete data and imprecision [23].…”
Section: Discussionmentioning
confidence: 99%
“…Other effective treatments include weight loss, oral appliances that hold the jaw forward during sleep, surgical modification of the pharyngeal soft tissues (i.e., lateral pharyngoplasty or uvulopalatopharyngoplasty) or facial skeleton to enlarge the upper airway, and exercise [ 5 , 7 ]. In addition, in recent years, comprehensive treatments that include general or specific muscle training have been suggested to lower the apnoea-hypopnea index (AHI) of the OSA patient population [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%